Mansonella ozzardi (Nematoda: Onchocercidae) in the riverine population of the Tefé River, State of Amazonia, Brazil - Jansen Fernandes Medeiros; Cristóvão Alves Costa; Alita Moura de Lima; Felipe Arley Costa Pessoa (Revista da Sociedade Brasileira de Medicina Tropical, 2014)
Introduction: This study assessed the prevalence of Mansonella ozzardi in riverine communities of the Tefé River, Amazonas, Brazil. Methods: The prevalence of M. ozzardi was estimated by microscopic examination of thick blood smears. Results: The M. ozzardi prevalence rate was 6.3% (19/300). Filarial infection was found in 8 of the 11 communities surveyed, with prevalence rates varying from 2.5% to 22.2%. Conclusions: Tefé is a region of oil and natural gas exploration, in which there is a high turnover of workers. Migration patterns may facilitate the dissemination of mansonelliasis to other regions.